KUALITAS PELAYANAN PESANTREN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS DAN CUSTOMER SATISFACTION INDEX TERHADAP KEPUASAN SANTRI - Nur Shofi’i, Eri; Nanda Noor Fajrin (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
Service is the main task of every educational institution that aims for the servants of the state and the servants of the community. This is clearly outlined in the opening of the 1945 Constitution, which covers 4 aspects of the basic service of educational institutions to the community which reads: Protecting the entire nation and all Indonesian blood to promote the general welfare and educate the life of the nation. The educational institution referred to in this research is Pondok Pesantren. This research was conducted as a description of the service at Pondok Pesantren Al-Ihya 'Ulumaddin Cilacap. The study was conducted with a survey through the dissemination of respondent questionnaires. After that, testing the validity and reliability of the questionnaire, then continued with the analysis of the data of the results of the study. The analysis is done by calculating the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The result of this research is that the majority of the public views the Conformity of Vision, Mission, Objectives, Leadership and Managerial Capabilities of the Leadership Council, Leadership and Managerial Capabilities Section, Benefits and Hygiene of Financing, Facilities and Infrastructure, Methods of Education and Teaching Activities, Methods of Delivery of Teaching and Learning Activities Materials, Methods of Delivery of Development and Extracurricular Activities, and Implementation of Annual Activities. Already has a very good competence in providing services to santri. There were 2 moderate items, 0 high priority items, 54 achievement preserve items, 3 low priority items, 16 items were too much. Based on CSI calculations of 81.93% showing that overall judging from all attributes, the service of Pondok Pesantren Al-Ihya' Ulumaddin Cilacap has entered the satisfactory criteria.